Two-stage cracking of metallic bi-layers on polymer substrates under tension. (1st March 2018) - Putz, B.; May-Miller, C.; Matl, V.; Völker, B.; Többens, D.M.; Semprimoschnig, C.; Cordill, M.J.
Abstract: This study demonstrates two-stage cracking of an Inconel‑silver film system on a flexible Teflon substrate under uniaxial tension. In situ fragmentation experiments revealed that primary fracture of the brittle 30 nm Inconel overcoat induced brittle, secondary fracture of the normally ductile 150 nm silver base layer. Good correlation exists between the ratios of primary and secondary saturation crack spacing and individual layer thicknesses. Two-stage cracking was confirmed by cross-sectional analysis and explained by different steady state energy release rates of the individual layers. The results further illustrate how brittle layers are detrimental to the mechanical behaviour of polymer-supported thin film multilayer structures. Graphical abstract: